A Job Training Report as an Assistant Journalist an International Division at Jawa Pos from 7th January to 15th February 2014 - Yesi Eva Susanti, 121101020 (2014)
Information or news is one of the people's needs. Besides to enlarge knowledge for what is going on around, information or news will help people to fullfill their social needs. Media exists to provide that needs, from both broadcasted and printed media. There are many channels in television, and also nespapers which are printed in daily. Jawa Pos newspaper is one of the national newpapers which provides its reader news from local, national, and international. The existence of international news in Jawa Pos newspaper gave the writer cahnce to do internship there. Doing internship in Jawa Pos newspaper helps the writer to improve her ability in English especially in translation, gives the writer chance to apply her knowledge from her study, and also gains new experience in media field that the writer has been interested in.